A Belgian consensus on the definition of a treat‐to‐target outcome set in psoriasis management. (2nd January 2020) - Grine, L.; de la Brassinne, M.; Ghislain, P.‐D.; Hillary, T.; Lambert, J.; Segaert, S.; Willaert, F.; ,; Lambert, J.
Abstract: Objective: Treat‐to‐target (T2T) is an algorithm to reach a predefined outcome. Here, we define a T2T outcome for moderate‐to‐severe psoriasis vulgaris. Methods: Briefly, the study included a literature review, discussions with key opinion leaders, recruitment of additional dermatologists with experience in managing moderate‐to‐severe psoriasis, 3 eDelphi survey rounds and a patient focus group. Relevant topics were selected during discussions prior to the survey for the statements. Surveys were based on the eDelphi methodology for consensus‐building using a series of statements. Consensus was defined as at least 80% of participants agreeing. A psoriasis patient focus group provided feedback on topic selection and outcome. Results: A total of 5 discussions were held, and 3 eDelphi rounds were conducted with an average of 19 participants per round. The T2T outcome was set assuming shared decision between patient and dermatologist, awareness and referral for comorbidities by the dermatologist and appropriate treatment adherence by the patient. We defined 'ideal' and 'acceptable' targets; the latter referring to conditions restricting certain drugs. The T2T outcome was multidimensional, including ≥ ΔPASI90/75 or PGA ≤ 1, itch VAS score ≤ 1, absence of disturbing lesions, DLQI ≤ 1/3, incapacity daily functioning VAS score ≤ 1, safety ≤ mild side‐effects and full/mild tolerability of treatment for the ideal and acceptable target, respectively. Finally, time to achieve the T2T outcome was set at 12 weeks after initiation for all treatments. At all times, safety should not exceed the presence of mild side‐effects. Conclusion: With this novel T2T composite outcome for psoriasis, clinicians and patients can make shared decisions on the treatment goals they envisage, as a guidance for future treatment steps – leading to a tight control management of the disease.